1999
DOI: 10.1016/s0378-1097(98)00539-4
|View full text |Cite
|
Sign up to set email alerts
|

Presence of erm gene classes in Gram-positive bacteria of animal and human origin in Denmark

Abstract: A classification of the different erm gene classes based on published sequences was performed, and specific primers to detect some of these classes designed. The presence of ermA (Tn554), ermB (class IV) and ermC (class VI) was determined by PCR in a total of 113 enterococcal, 77 streptococcal and 68 staphylococcal erythromycin resistant isolates of animal and human origin. At least one of these genes was detected in 88% of the isolates. Four isolates contained more than one erm gene. ermB dominated among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 17 publications
5
65
0
Order By: Relevance
“…Target modification is the most widespread resistance mechanism and refers to the dimethylation of an adenine residue in the 23S rRNA. Four rRNA methylase (erm) genes, designated erm(A), erm(B), erm(C), and erm(F), have until now been identified in staphylococci of animal origin [14,20,27,38,39,73,85,90,103,104,106].…”
Section: Resistance To Macrolides Lincosamides and Streptograminsmentioning
confidence: 99%
See 2 more Smart Citations
“…Target modification is the most widespread resistance mechanism and refers to the dimethylation of an adenine residue in the 23S rRNA. Four rRNA methylase (erm) genes, designated erm(A), erm(B), erm(C), and erm(F), have until now been identified in staphylococci of animal origin [14,20,27,38,39,73,85,90,103,104,106].…”
Section: Resistance To Macrolides Lincosamides and Streptograminsmentioning
confidence: 99%
“…Studies of the occurrence of the different erm genes among animal staphylococci [14,20,27] showed that erm(C) genes were frequently seen in S. hyicus and other porcine staphylococci [20,27], but also in many staphylococcal species from various animal sources [38,39,73,85,90,106] while erm(B) genes were the dominant erm genes in canine S. intermedius isolates [8,20]. Genes of the class erm(F) have so far only been detected in a few S. intermedius iso-lates from pigeons [14] and erm(A) genes have also only been identified in single animal staphylococcal isolates, mainly of avian origin [47,103] and porcine origin [27].…”
Section: Resistance To Macrolides Lincosamides and Streptograminsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to macrolides in other organisms may result from target modification, enhanced drug efflux, and drug inactivation. The most widespread mechanism of macrolide resistance is target modification mediated by erythromycin ribosome methylase genes, which prevents macrolide, lincosamide, and type B streptogramin (MLS B ) antimicrobials from binding to 23S ribosomal RNA (rRNA) (Jensen et al, 1999;Weisblum, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Vancomycinresistant enterococci (VRE) have been identified as an important cause of hospital-acquired infection (Goossens, 1998) and have been related to animal production (Aarestrup, 1995;Klare et al, 1995;Robredo et al, 1999;Stobbering et al, 1999;Teuber and Perreten, 2000). Enterococci isolates from animal and human origins have also been reported to carry erythromycin resistance genes (Jackson et al, 2004;Jensen et al, 1999). Consequently, resistance to these two antibiotics could be potentially transmitted through the bacterial population of wastewater and sludge, particularly in sewage treatment plants which have a high concentration of bacteria of distinct fecal origin.…”
Section: Introductionmentioning
confidence: 99%